Characteristics of full compensation and its association with total astigmatism: A cross-sectional study - Wu, Ziyun; Hu, Yuanyuan; Xu, Zihang; Sun, Wei; Wang, Yirong; Shao, Zhen; Liu, Yi; Yu, Mingkun; Si, Peiran; Huo, HuanHuan; Wang, Xingrong; Bi, Hongsheng (Frontiers in Public Health, 2023)
Objective: To evaluate the characteristics of full compensation of internal astigmatism (IA), and investigate associations between full compensation and the prevalence of total astigmatism (TA). Methods: With random cluster sampling based on a school-based cross-sectional design, children aged 4 to 18 years were recruited in September 2020, Shandong Province, China. TA, anterior corneal astigmatism (ACA), and IA were converted to vectorial components (J0, J45), followed by an assessment of the compensatory effect of ACA by IA. Astigmatism was defined as a cylinder that was better than or equal to 0.75 diopters (D), expressed as a positive cylinder form. Results: Out of 4,494 eligible children, data of 4,145 children (92.3%, 9.23±3.15 years, 50.4% boys) were included in the statistical analysis. Both magnitude (0.52 ±0.55 D) and prevalence of TA (27.9%) increased significantly with age (Ptrend<0.001). The distribution of full compensation in J0 and J45 components were similar (22.1% and 25.6%, respectively), which decreased with age (Ptrend<0.001). The closer the refractive status was to emmetropization, the higher the proportion of full compensation and the lower the prevalence of TA were. Shorter axial length, better UDVA, smaller TA, and longer average corneal curvature radius were associated with full compensation (P<0.05). Higher TA was associated with a worse UDVA (OR=1.03). Conclusions: The prevalence of TA gradually increased with age, and showed a U-shaped distribution with increased refraction. Full compensation was a protective factor for TA and UDVA. This indicated that considering the compensatory effect of IA is vital for astigmatism correction in clinical work, which may improve the visual quality.